ANALYSIS OF DEVELOPMENT CHARACTERISTICS OF RAIL WEAR DISTRIBUTION OF SMALL RADIUS CURVE SECTION IN METRO - LEI ZhenYu; WANG ZhiQiang (Jixie qiangdu)
Based on vehicle-track coupled dynamics and Archard wear models,the influence of different axle loads,friction coefficients and running speeds on the rail wear characteristics of small radius curve section in metro were analyzed and discussed.The results indicated that the left rail wear concentrated on the shoulder and the right rail wear concentrated on the middle of the rail head,and the cumulative wear amplitude of the left rail was greater than that of the right rail. When the axle load increases,both the left and right rail wear increases. When the friction coefficient increases,both the left and right rail wear increases. When the speed increases,the left rail wear increases and the right rail wear tends to decrease. Relative to the speed of 80 km/h,the left rail wear tends to develop towards the shoulder at 40 km/h,the middle of the rail head at 60 km/h,and the right rail wear is basically unchanged. Through analysis of the prediction of rail profile,it can be concluded that the left rail wear concentrates on the middle and shoulder of rail head. The wear on the shoulder is relatively large,and the maximum value is located at the rail transverse position 18. 506 mm,reaching 0. 820 mm. The right rail wear appears to varying degrees. The wear on the middle of the rail head is relatively large,and the maximum value is located at the rail transverse position 2. 082 mm,reaching 0. 170 mm.